Improved electrochemical performance of SiO2-coated Li-rich layered oxides-Li1.2Ni0.13Mn0.54Co0.13O2 - Jeffin James Abraham (14151165) (2022)
Lithium-rich layered oxides (LLOs) such as Li1.2Ni0.13Mn0.54Co0.13O2 are suitable cathode materials for future lithium-ion batteries (LIBs). Despite some salient advantages, like low cost, ease of fabrication, high capacity, and higher operating voltage, these materials suffer from low cyclic stability and poor capacity retention. Several different techniques have been proposed to address the limitations associated with LLOs. Herein, we report the surface modification of Li1.2Ni0.13Mn0.54Co0.13O2 by utilizing cheap and readily available silica (SiO2) to improve its electrochemical performance. Towards this direction, Li1.2Ni0.13Mn0.54Co0.13O2 was synthesized utilizing a sol–gel process and coated with SiO2 (SiO2 = 1.0 wt%, 1.5 wt%, and 2.0 wt%) employing dry ball milling technique. XRD, SEM, TEM, elemental mapping and XPS characterization techniques confirm the formation of phase pure materials and presence of SiO2 coating layer on the surface of Li1.2Ni0.13Mn0.54Co0.13O2 particles. The electrochemical measurements indicate that the SiO2-coated Li1.2Ni0.13Mn0.54Co0.13O2 materials show improved electrochemical performance in terms of capacity retention and cyclability when compared to the uncoated material. This improvement in electrochemical performance can be related to the prevention of electrolyte decomposition when in direct contact with the surface of charged Li1.2Ni0.13Mn0.54Co0.13O2 cathode material. The SiO2 coating thus prevents the unwanted side reactions between cathode material and the electrolyte. 1.0 wt% SiO2-coated Li1.2Ni0.13Mn0.54Co0.13O2shows the best electrochemical performance in terms of rate capability and capacity retention. Other Information Published in: Journal of Materials Science: Materials in Electronics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10854-020-04481-6